2021
DOI: 10.3390/cells10092384
|View full text |Cite
|
Sign up to set email alerts
|

Cep192, a Novel Missing Link between the Centrosomal Core and Corona in Dictyostelium Amoebae

Abstract: The Dictyostelium centrosome is a nucleus-associated body with a diameter of approx. 500 nm. It contains no centrioles but consists of a cylindrical layered core structure surrounded by a microtubule-nucleating corona. At the onset of mitosis, the corona disassembles and the core structure duplicates through growth, splitting, and reorganization of the outer core layers. During the last decades our research group has characterized the majority of the 42 known centrosomal proteins. In this work we focus on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…Thus, it is not far-fetched to presume that NUP93 could also bind to the centrosomal fraction of NUP53 in Dictyostelium. Due to its central localization it can be assumed that NUP53 interacts with one of the core components, either with Cep192 [40] in the outer layers, or one of the central layer proteins CP39, CP75 or CP91 [16]. For CP75 it has been speculated to play a role in the insertion of the centrosome into the nuclear envelope at the onset of mitosis, and it is conceivable that NUP53 assists the centrosomal protein in this function by virtue of its membrane-shaping properties [41].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is not far-fetched to presume that NUP93 could also bind to the centrosomal fraction of NUP53 in Dictyostelium. Due to its central localization it can be assumed that NUP53 interacts with one of the core components, either with Cep192 [40] in the outer layers, or one of the central layer proteins CP39, CP75 or CP91 [16]. For CP75 it has been speculated to play a role in the insertion of the centrosome into the nuclear envelope at the onset of mitosis, and it is conceivable that NUP53 assists the centrosomal protein in this function by virtue of its membrane-shaping properties [41].…”
Section: Discussionmentioning
confidence: 99%
“…Three proteins of the core structure, CP39, CP91 and CP75, were attributed to the central layer since they all disappear from mitotic centrosomes [33,53]. This attribution was later confirmed by ExM [54]. All three appear to be essential, since their depletion caused severe phenotypes, and knockout attempts failed altogether.…”
Section: Central Core Layermentioning
confidence: 88%
“…As in case of CP148, depletion of CDK5RAP2 causes disintegration of the corona and the appearance of multiple, cytosolic microtubule nucleation complexes [71]. Superresolution microscopy indicated that it forms the interface between the corona and the layered core, since its localization closely matches that of the outer core layer component Cep192 [54].…”
Section: γ-Tubulin and Its Interactorsmentioning
confidence: 91%
See 2 more Smart Citations